THE MEANING OF THE SIGN OF PASOLA SHOW IN WAIHURA VILLAGE WANOKAKA SUB-DISTRICT, WEST SUMBA REGENCY: A STUDY OF SEMIOTICS - Ristoforus U.P Jagalimu; Ni Wayan Kasni (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
This paper discusses the study of semiotics on the meaning of the sign of Pasola show in Waihura Village Wanokaka District, West Sumba Regency. This study aims at describing how the meaning and form of the sign in the implementation of Pasola show in Wanokaka community. This study was conducted on the basis of Pierce's semiotics theory in Aart (1993). The design of this research was descriptive qualitative. The data was obtained from the speech of the performers of Pasola called Rato. Method and technique of data collection were observation and interview. Observation was used to obtain the data of the implementation process and the signs involved in the Pasola show, while the interview was used to obtain the spoken data used and the meaning in Pasola's references. From the results of data analysis it was found that in Pasola show there are twenty marks, such as mamoli (earring), nibbu (spear), profit (drum), katopu (machete), karera (bag), katala (gong), whung, koba (bowl), kalabi (shirt), rowa rara (red sash), rowa metung (black sash), laiku (rope), leli (ring), reba (place to eat), winu (betel nut), rato (Customary ruler), arera (betel nut), lagoru (dribble), rahi dara (horse control), regi (cloth), horse equipments, Pasola player, lado, hela, kadu watu, Rato position. The meaning of these signs is as a symbol of fertility for women, symbolizing splendor. Dragon symbolizes the entry of the holy month that all the restrictions must be followed, symbolizing the unity of society in running the life of society, symbolizing the majesty of a king, the moon gives a hint of the passage of Pasola, the symbol of life Wanokaka society.